Stormwater sediment monitoring in infiltration facilities: a convenient method for assessing accumulation rates and mitigating environmental impact - Chabert, Milèna; Large, Gautier; Tedoldi, Damien; Lakel, Abdelkader; Fardel, Alexandre; Lipeme Kouyi, Gislain; Gasc, Aurore; Nguyen, Emilie; Chatain, Vincent (Journal of cleaner production, 2025)
Infiltration-based facilities are increasingly implemented for stormwater management in urban areas. They notably contribute to pollution mitigation by retaining particulate matter through settling and/or filtration, which can impair their hydraulic performance and treatment efficiency. Therefore, anticipating future maintenance needs is crucial, and implies characterizing sediment buildup. The latter can be assessed by targeting particle load in runoff: this is usually achieved through continuous monitoring and/or stormwater sampling. As these methods appear unsuitable for routine assessments at the scale of urban territories, this study presents a convenient, cost-effective method based on sediment height measurements after a certain accumulation period. The consistency of this approach was validated on a pilot site by comparing the estimate with continuous monitoring outputs. Mass estimates were supported by an in-depth analysis of sediment dry bulk density, ranging from 0.4 to 1.2 g/cm3. The method also provides reliable estimates of the average annual particle load for urban catchments, as demonstrated through its application to nine sites in France and comparison with literature data. Based on this dataset, particle load estimates show high variability, typically ranging from 50 to 2000 kg/ha impervious surface/year. Loads are unlikely to exceed 1000 kg/haimp/yr in less productive environments (e.g., residential areas) and 2000 kg/haimp/yr in more productive ones (e.g., high-traffic roads). As contaminants tend to associate with particulate matter, this study paves the way for their quantification. [Display omitted] •This methodology can support convenient data collection and statistical modeling.•Results are consistent with continuous monitoring and literature.•Particle load estimates mostly range between 50 and 2000 kg/haimp/yr.•Practical outcomes can help mitigating environmental impact of contaminated sediment.